Exposure–Response Analysis of Overall Survival for Tremelimumab in Unresectable Malignant Mesothelioma: The Confounding Effect of Disease Status. Issue 5 (12th April 2019) - Baverel, Paul; Roskos, Lorin; Tatipalli, Manasa; Lee, Nancy; Stockman, Paul; Taboada, Maria; Vicini, Paolo; Horgan, Kevin; Narwal, Rajesh
Abstract : Tremelimumab, an anti‐cytotoxic T‐lymphocyte antigen‐4 monoclonal antibody that enhances T‐cell activation, was evaluated in a randomized, double‐blind, placebo‐controlled, phase IIb study (NCT01843374) in patients with unresectable malignant mesothelioma. The study demonstrated no clinically meaningful differences in overall survival (OS). The objective of this analysis was to evaluate the relationship of exposure with OS. A population pharmacokinetic (PK) model adequately described the PK data. Three factors (sex, C‐reactive protein, and baseline tumor size) were identified as statistically significant PK predictors ( P  < 0.05 on clearance). A positive association between exposure and OS was observed. However, an association between key baseline factors with OS (regardless of treatment) and imbalances in prognostic factors favoring patients with higher exposure (upper vs. lower PK quartile) was seen. Taken together, these results suggest that the exposure OS relationship observed for tremelimumab in mesothelioma is likely spurious rather than a true association of exposure with efficacy.